Visual conservation treatment dilemmas in neuroblastoma with bilateral blindness - Haiyan Cheng; Yu Lin; Wei Yang; Xiaofeng Chang; Jun Feng; Shen Yang; Shan Liu; Tong Yu; Xiaojiao Peng; Panpan Zheng; Chengyue Zhang; Haiwei Jia; et al. (Discover Oncology, 2024)
Abstract Objective To investigate the clinical features, treatment strategies, and prognosis of neuroblastoma with bilateral blindness. Methods The clinical data of five patients with bilateral blindness neuroblastoma admitted to Beijing Children’s Hospital from April 2018 to September 2020 were retrospectively collected to summarize their clinical characteristics. Results All patients were female and the median age at presentation was 25 (23, 41) months. The median intervention time from the onset of symptoms of bilateral blindness to the start of treatment was 10 (10, 12) days. All five cases were staged as stage M and grouped as high risk. Four cases were MYCN gene amplification and one case was MYCN acquisition. Five children were treated according to a high-risk neuroblastoma treatment protocol. Four children did not recover their vision after treatment, and one case improved to have light perception. All patients were effectively followed up for a median of 20 (12, 31) months, with three deaths, one tumor-free survival, and one recurrent tumor-bearing survival. Conclusion Neuroblastoma with bilateral blindness is rare in the clinic, mostly in children of young age, and is often associated with MYCN amplification and multiple metastases. Early hormone shock therapy and optic nerve decompression are beneficial for preserving the child’s vision. A joint multi-disciplinary treatment may help in the formulation of treatment decisions. Achieving a balance between good visual preservation and survival within the short optic nerve neurotherapeutic window is extremely challenging.